Glutamine-assisted synthesis of Cu-doped CeO2 nanowires with an improved low-temperature CO oxidation activity1. Issue 36 (23rd April 2015) - Wang, Juan; Lin, Siwen; Han, Zeye; Liu, Yuping
<x xml:space="preserve">Abstract</x> Glutamine (GLN)-assisted Cu-doped CeO2 nanowires exhibit an outstanding performance for CO oxidation and can completely convert CO at 90 °C.